Currency Regimes and the Carry Trade. (October 2019) - Accominotti, Olivier; Cen, Jason; Chambers, David; Marsh, Ian W.
Abstract : This study exploits a new long-run data set of daily bid and offered exchange rates in spot and forward markets from 1919 to the present to analyze carry returns in fixed and floating currency regimes. We first find that outsized carry returns occur exclusively in the floating regime, being zero in the fixed regime. Second, we show that fixed-to-floating regime shifts are associated with negative returns to a carry strategy implemented only on floating currencies, robust to the inclusion of volatility risks. These shifts are typically characterized by global flight-to-safety events that represent bad times for carry traders.